Aeternus Augustus in der Titulatur der römischen Kaiser im Späten 3. Und im 4. jh. - Balbuza, Katarzyna (Studia Europaea Gnesnensia, 2017)
The article is concerned with the title aeternus Augustus and its position in Roman imperial titulature at the end of the third and during the fourth century A.D. Modern authors tend to rate this title among the so-called unofficial imperial titulature, mainly due to the fact that it served to admire the emperor. The paper discusses forms and methods of addressing the emperor who was determined by the appellation aeternus Augustus. The analysis of these enables to appoint, out of the emperors of the discussed period, those few who were officially specified as aeterni.